Letter - Winstanley, E.
030-0146-001 Telegraphic Address, Inland - "Wholesale, Manchester." Foreign - "Copexport, Manchester." Telephone: Blackfriars 1212. Extension No. 87 Please address your reply: CO-OPERATIVE WHOLESALE SOCIETY LIMITED, EXPORTERS, BUYING AND SHIPPING AGENTS, 1, BALLOON STREET, MANCHESTER, 4. Cable codes: A.B.C. 6th and 7th editions; Western Union 8 Letter; Bentley Complete Phrase; Bentley Second Phrase; A.I. Marconi, and private. Our reference EXPORT HL/HP. 1179 24th June, 1938. Your reference The Trades Union Congress, Transport House, Smith Square, LONDON S.W.1. Dear Sirs, We have pleasure in acknowledging receipt of your letter of the 23rd instant, reference HVT/FC/470, and thank you for your order for 5,600 pairs of Children's Sandals which we are placing into work for immediate execution. We may be able to effect shipment to Rouen by s.s. NEW PIONEER from Garston on June 30th, but if this is not possible, we can definitely assure you that delivery will be effected by the following steamer on July 7th. Your remarks respecting the present tendency of the sandals to chafe the heels is being given attention, and if it should be necessary for the sandals to be specially made, it may be that our Works will be able to eliminate this fault, and we will communicate their observations on this point in due course. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/30/146